Exploring Environmental Damage in Novel The Color Purple by Alice Walker and Bekisar Merah by Ahmad Tohari: A Literature Ecocritics Review - Olga A. Rorintulus; Maissy Jearmita Manuas; Ignatius J. C Tuerah (Journal of English Language Teaching, Literature and Culture, 2022)
This study aims to discuss what environmental damage is discussed in the novels The Color Purple by Alice Walker and Bekisar Merah by Ahmad Tohari. In this study using a qualitative method as the method, data collection is done by analyzing the dialogues in the novel and then writing it down and researching it. The use of supporting sources is also applied in this study. For further research, it is suggested to put more emphasis on what environmental damage occurred in the novel and compared it with environmental damage in the real world. Comparisons like this are very interesting to study, but due to the lack of available sources, it is requested to conduct further research.